Awareness and Knowledge of Patient Safety Among Healthcare physician in Prince Abdulaziz bin Musaed Hospital, Arar, Saudi Arabia: A Cross-Sectional Study - Alanazi Saleh Farhan , M., Heba Alqurashi PhD, MSc, BSc (Journal of International Crisis and Risk Communication Research, 2024)
This study explores the awareness and knowledge of patient safety among physicians at Prince Abdulaziz bin Musaed Hospital in Arar, Saudi Arabia, focusing on identifying strengths and gaps in the hospital’s safety culture. Patient safety is a critical component in healthcare, and understanding physicians' perspectives on safety protocols is essential for improving care quality and reducing adverse events. Using a cross-sectional survey methodology, data were gathered from 92 physicians across various specialties within the hospital. The survey included questions on teamwork, staffing, error reporting, and communication during patient transitions. The results indicate a generally supportive safety culture, with strong teamwork and leadership commitment to patient safety perceived by the majority of respondents. However, significant challenges were noted, particularly related to staffing adequacy, inconsistent error reporting, and communication during patient handovers. Over two-thirds of participants reported that staffing shortages impacted their ability to deliver safe care, while underreporting of near-miss events indicated a need for a non-punitive error-reporting culture. Communication issues during patient transitions were also highlighted, suggesting a need for standardized handover protocols. The study concludes that while a solid foundation for patient safety exists, addressing staffing issues, promoting consistent error reporting, and standardizing communication can strengthen the hospital's safety culture. These findings have implications for healthcare facilities in similar settings, emphasizing the importance of a proactive approach to patient safety that includes sufficient staffing, supportive leadership, and a culture that encourages learning from errors to enhance patient care quality and safety outcomes.